Antioxidant activity of different cheese-honey combinations before and after in vitro gastrointestinal digestion. (September 2020) - Simonetti, Amalia; Perna, Annamaria; Grassi, Giulia; Gambacorta, Emilio
Abstract: This study aimed to evaluate the effect of different cheese-honey combinations on antioxidant activity before and after in vitro gastrointestinal digestion, using the 2, 2′-azino-bis-3-ethylbenzothiazoline- 6-sulfonic acid (ABTS), and ferric-reducing antioxidant power (FRAP) assays. Honey addition significantly enhanced the antioxidant activity of cheese samples (P < 0.05). The antioxidant activity of in vitro digested samples was significantly lower than the undigested ones. However, digested cheese-honey combination showed a percentage decrease of antioxidant activity lower than plain cheese. The cheese and honey types affected the percentage decrease of antioxidant activity in the digested samples, this is mainly due to the bioaccessibility of the honey polyphenols after digestion. Sensory analysis showed that all cheese-honey combinations were well accepted by the consumers, the health information on higher antioxidant capacity of dark honeys has not influenced the degree of acceptability of consumers, who preferred the cheese - clear honey combinations. Graphical abstract: Image 1 Highlights: Honey addition significantly enhanced the antioxidant activity of cheese samples. In vitro digestion led to a reduction of antioxidant activity of all samples. Digested cheese-honey showed a lower decrease of antioxidant activity than digested cheese. Despite the health information on dark honeys the consumers preferred cheese - clear honey combinations.